Artikel Pengaruh Pemberian Aloe Vera Terhadap Toksisitas (Efek Samping) Kulit Pada Pasien Kanker Payudara Yang Di Radiasi Di Radioterapi: The Effect of Giving Aloe Vera on Skin Toxicity (Side Effects) in Breast Cancer Patients Who are Radiated in Radiotherapy - Rosita (Dohara POAJ, 2025)
Introduction: Breast cancer patients who are undergoing radiation therapy are susceptible to skin toxicity. Methods: Using a quasi-experimental method. Pre-test-post-test research type. Results: Based on the results of research on the effect of administering aloe vera on skin toxicity (side effects) in breast cancer patients who were exposed to radiotherapy with a p-value = 0,000 < α (0,05). Discussion: There is an influence between administering aloe vera on skin toxicity (side effects) in breast cancer patients who are exposed to radiotherapy.